Are All Ratings Created Equal? The Impact of Issuer Size on the Pricing of Mortgage‐Backed Securities - HE, JIE (JACK); QIAN, JUN (QJ); STRAHAN, PHILIP E. (Journal of Finance, 2012)
ABSTRACT Initial yields on both AAA‐rated and non‐AAA rated mortgage‐backed security (MBS) tranches sold by large issuers are higher than yields on similar tranches sold by small issuers during the market boom years of 2004 to 2006. Moreover, the prices of MBS sold by large issuers drop more than those sold by small issuers, and the differences are concentrated among tranches issued during 2004 to 2006. These results suggest that investors price the risk that large issuers received more inflated ratings than small issuers, especially during boom periods.